Exploring Knowledge of English Speaking Strategies in 8th and 12th Graders - Claudio Díaz Larenas (Universidad Nacional de Colombia, 2011)
This article presents a research study that analyses eighth and twelfth graders' knowledge of speaking strategies to communicate in English. The Oral Communication Strategy Inventory, developed by Nakatani in 2006, was applied to 108 students belonging to the public, semi-public and private educational sectors in Chile. The findings show that 8th graders claim to have broader knowledge of speaking strategies than 12th year secondary students, and the knowledge of speaking strategies of elementary and secondary school students does not vary depending on the type of school: public, semi public and/or private.